Habitat e biologia reprodutiva de Steindachneridion melanodermatum Garavello, 2005, espécie endêmica do Rio Iguaçu - Assumpção, Lucileine de (2018)
The lack of knowledge on the biological and ecological aspects of Steindachneridion melanodermatum, an endangered fish species, has made it difficult to plan and implement specific conservation and management strategies. Thus, this study determines the locals of occurrence of the species and characterizes its preferred habitat, the deep pools, through bathymetric analyzes, and addresses information on reproductive tactics such as length of first maturation, spawning type and period reproductive. The study area comprised the region of the Lower Iguaçu River, a stretch of approximately 190 km in length, downstream from the Salto Caxias Hydroelectric Power Plant to upstream of the Iguaçu Falls, including some tributaries, where 27 sampling sites were established. In the period from September 2012 to December 2016, a total of 182 specimens of S. melanodermatum were sampled with total length ranging from 21 to 102 cm and weight from 82.8 to 15,670.0g. The greatest abundances of the species were recorded in the pools with depths from 22 to 25m, especially in the deep pool called Poço Preto located in the Conservation Unit of the Iguaçu National Park. Along the sampled stretch, 23 pools with maximum depths ranging from 5 to 25 m were identified, of these 19 pools are located along the main channel of the Iguaçu River and 03 pools in the tributaries. The reproductive period of the species corresponded from June to September, with reproductive peaks in September for females and August for males. Spawning was considered of the total type and absolute fecundity ranged from 30,673.26 to 167,726.08 oocytes per female. The first maturation size (L50) was 39.5 cm for females and 43.9 cm for males. The characterization and mapping of the deep pools in the Iguaçu River were fundamental to determine areas of conservation or sanctuary, in order to guarantee that the habitats of the species are protected. The information obtained here on reproductive biology will help to elaborate specific measures and criteria for conservation of this species.